Cross‐sectional survey of workplace stressors associated with physician burnout measured by the Mini‐Z and the Maslach Burnout Inventory. (21st January 2019) - Olson, Kristine; Sinsky, Christine; Rinne, Seppo T.; Long, Theodore; Vender, Ronald; Mukherjee, Sandip; Bennick, Michael; Linzer, Mark
Abstract: Rising physician burnout has adverse effects on healthcare. This study aimed to identify remediable stressors associated with burnout using the 10‐item Mini‐Z and the Maslach Burnout Inventory (MBI), and to compare performance of the Mini‐Z's single‐item burnout metric against the 22‐item MBI. Surveys were emailed to 4, 118 clinicians affiliated with an academic health system; 1, 252 clicked the link, and 557 responded (completion rate 44%). Four hundred seventy‐five practicing physicians were included: academic faculty (372), hospital employed (52), and private practitioners (81). Prevalence of burnout via the MBI was 56.6%. Predictors of burnout were poor control over workload [OR = 8.24, 95% CI 4.(81, 14.11)], inefficient teamwork [OR = 7.61, 95% (CI 3.28, 17.67)], insufficient documentation time [OR = 5.83, 95% (CI 3.35, 10.15)], hectic‐chaotic work atmosphere [OR = 3.49, 95% (CI 2.12, 5.74)], lack of value‐alignment with leadership [OR = 3.27, 95% (CI 2.12, 5.74)], and excessive electronic medical record time at home [OR = 1.99, 95% CI (1.21, 3.27)]. Academic faculty experienced more burnout than private practitioners (59.9% vs. 42.0%, p  = 0.013). Odds of burnout associated with stressors were generally concordant via Mini‐Z's burnout metric versus the MBI. The Mini‐Z is a brief, valid method to identify stressors associated with burnout and guide interventions.